Solid waste management : principles and practice - Chandrappa, Ramesha; Das, Diganta Bhusan (New York : Springer-Verlag Berlin Heidelberg, 2012)
While thousands of people depend on waste for their livelihood throughout the world, many others face problems due to poor waste management. In this context solid waste has not remained an issue to be tackled by the local urban bodies alone.
1. Introduction -- 2. Waste quantities and characteristics -- 3. Storage and collection -- 4. Materials recovery and recycling -- 5. Disposal -- 6. Biomedical waste -- 7. Hazardous waste -- 8. Waste from electrical and electronic equipment -- 9. Waste from industry and commercial activity -- 10. Radio active waste -- 11. Health and safety issues -- 12. Environmental issues -- 13. Issues in disaster affected area -- 14. Solid waste and livelihood -- Appendix -- Glossary -- Index.
Includes index.
Keywords: SOLID WASTE; WASTE DISPOSAL; WASTE TREATMENT; PRODUCT SHAPE -- ELECTRONIC TEXT; TARGET GROUP -- RESEARCH